Tablet type carbonaceous coating carrier as well as preparation method and application thereof
By thermal activation and hydrothermal carbonization of biomass fibers, combined with high-temperature sintering and coating sealing treatment, a tablet-based carbonaceous coating carrier was prepared, which solved the problems of existing carriers being prone to moisture absorption and rust and surface adhesion of grease, achieving high stability of the carrier and reusable multiple times, reducing production costs.
Patent Information
- Application Number
- CN202411595710.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
AI Technical Summary
Existing vacuum coating carrier materials such as steel wire wool are prone to moisture absorption and rust, and the adhesion of oil and fat compounds on the surface affects the performance of the agent, making it difficult to achieve multiple reuses, resulting in high production costs and equipment damage.
Biomass fibers are used as the carbonaceous coating carrier, and the pore structure and functional group content are improved through thermal activation and hydrothermal carbonization treatment, combined with high-temperature sintering and coating sealing treatment, so as to improve the stability and reusability of the carrier.
It significantly improves the stability and reusability of the coating carrier, reduces the loss of agents and pills during vacuum packaging, reduces production costs, and maintains good physical and chemical properties.
Smart Images

Figure CN119528593A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of vacuum coating, and relates to a tablet-type carbonaceous coating carrier and a preparation method and application thereof. Background Art
[0002] Vacuum evaporation coating refers to a deposition technology that uses the heat energy of a film material heating device (called an evaporation source) under vacuum conditions to evaporate a certain substance and deposit it on the surface of the substrate material. Among them, the coating carrier plays a very important role. It is required to be pure and non-deteriorated, not react with the evaporation agent, and have high temperature resistance.
[0003] Chinese patent application CN114310184A provides a method for preparing a vacuum-coated pill carrier. The technology uses stainless steel micro-wire felt as a carrier and uses stamping technology to press it into a metal crucible to obtain a pill carrier, which can effectively ensure the stability of the pill properties and greatly save labor costs. However, steel wool made of low-carbon steel is very easy to absorb moisture and rust and deteriorate, which makes it difficult to reuse it after completing a coating experiment. In addition, during the production process, oily compounds will adhere to the surface of the steel wool to a greater or lesser extent, which seriously affects the performance of the evaporation agent.
[0004] Carbon material is a functional material with good pore structure, specific surface area and thermal conductivity, and is widely used in energy, environment, medicine and other fields as a carrier material, such as Chinese patent CN112331862 A, Chinese patent CN113506885 A, Chinese patent CN 101831420 A, etc. Therefore, preparing carbon material into a coating carrier is expected to solve many problems of existing steel wool coating carriers, and achieve the purpose of multiple reuse of coating carriers, thereby reducing costs and increasing efficiency in industrial production. Summary of the invention
[0005] In view of the problems existing in the prior art, the first purpose of the present invention is to provide a tablet-type carbonaceous coated carrier, which is based on biomass fiber and undergoes thermal activation and hydrothermal carbonization treatment to effectively improve the pore structure and surface functional group content, greatly improve the affinity between the carrier and the binder, ensure the stability of the carrier and enhance the drug adhesion ability. In addition, through coating and sealing treatment, the drug loss and pill breakage during vacuum packaging can be effectively reduced, giving the carrier excellent reusability and greatly reducing production costs.
[0006] The second object of the present invention is to provide a method for preparing a tablet-type carbonaceous coated carrier, which improves the reusability, stability and wear resistance of the coated carrier through wet pyrolysis, coordinated high-temperature sintering and coating and sealing treatment; the method is simple and easy to operate, has low production cost, and has the potential for industrial production.
[0007] The third object of the present invention is to provide an application of a tablet-type carbonaceous coating carrier, which is used as a coating carrier in vacuum evaporation coating, which not only reduces the loss of medicine and pill breakage during vacuum packaging, but also greatly improves the stability and reusability of the coating carrier while ensuring the coating performance.
[0008] In order to achieve the above technical objectives, the present invention provides a method for preparing a tablet-type carbonaceous coated carrier, which comprises the following steps: crushing biomass fibers into short fibers and dispersing them into an activation solution, sequentially performing thermal activation treatment and hydrothermal carbonization treatment to obtain activated fiber carbon; the activated fiber carbon is mixed with a binder, pressed into shape, and subjected to high-temperature sintering to obtain a fiber carbon disc; a coating agent is applied to the surface of the fiber carbon disc for overall coating and sealing treatment, and after drying, the top is cut off along the thickness direction to obtain the obtained product.
[0009] The technical solution of the present invention successfully endows the activated fiber carbon with rich pore structure and oxygen-containing functional groups by subjecting the biomass fiber to thermal activation and hydrothermal carbonization treatment, acid-base etching and high temperature and high pressure conditions, significantly improving the contact surface and bonding force between the activated fiber carbon and the adhesive, so that it can achieve the purpose of firm bonding under the action of a very small amount of adhesive, thereby helping to improve the adhesion ability of the coating agent. The high-temperature sintering treatment can not only further enrich the pore structure of the activated fiber carbon and improve the ability to adhere to the coating agent, but also remove the oxygen-containing functional groups that are not combined with the adhesive introduced in the early stage, thereby improving the stability of the coating carrier. In addition, the present invention uses a coating agent to coat and seal the activated fiber carbon after pressing it into shape, so that an effective isolation layer is formed on the surface of the carrier to prevent the coating agent from scattering, and can also effectively avoid the loss and rupture of the crucible to which the coating agent is dripped during the vacuum packaging process, significantly improving the reusability of the coating carrier.
[0010] Experiments have found that using biomass fiber as a carbon source has a better effect than using organic solid wastes such as waste rubber, sludge, and coal. It can further improve the stability of the carrier and the adhesion ability to the coating agent, effectively ensuring the performance of the film layer. At the same time, the inventors found that when using carbon fiber to replace biomass fiber, on the one hand, the carbon fiber composed of polymer materials cannot be crushed into short fibers, which results in the carrier obtained after tableting and sintering being dense and compact, and not suitable for the attachment of reagents; on the other hand, the carbon fiber cannot form a rich pore structure and oxygen-containing functional groups through thermal activation treatment and hydrothermal carbonization treatment, so the affinity with the binder is significantly reduced.
[0011] As a preferred solution, the biomass fiber is at least one of bamboo fiber, reed straw fiber, ramie straw fiber, cotton stalk fiber and coconut shell fiber. The biomass fiber selected in the present invention is easier to obtain short fiber carbon material, and more preferably, the biomass fiber is reed straw fiber.
[0012] As a preferred solution, the activation solution comprises at least one activator selected from the group consisting of sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, hydrogen peroxide, sodium hydroxide and potassium hydroxide. Further preferably, the activation solution is sulfuric acid.
[0013] As a preferred solution, the mass ratio of the activator to water in the activation solution is (1-10): (2-10). It is further preferred that the mass ratio of the activator to water in the activation solution is (3-6): (2-4); and it is particularly preferred that it is 5:3. Within the preferred activator concentration range of the present invention, a better activation effect can be obtained with a smaller amount of activator.
[0014] As a preferred solution, the mass ratio of the biomass fiber to the activation solution is (1-10): (50-80); experiments have found that under the above preferred conditions, the biomass fiber can be further activated to have a richer pore structure and surface functional groups, which is conducive to promoting the combination of activated fiber carbon and the binder, making the performance of the carrier more stable. When the mass ratio of the biomass fiber to the activation solution is too low, it will lead to too high a residual activation solution, resulting in excessive pressure for hydrothermal carbonization, posing a safety risk; and when the mass ratio is too low, it will lead to insufficient contact between the activation solution and the biomass fiber during hydrothermal carbonization, thereby affecting the degree of carbonization and specific surface area. It is further preferred that the mass ratio of the biomass fiber to the activation solution is (1-3): (50-60).
[0015] As a preferred solution, the length of the short fibers is 1 to 3 mm. The preferred short fiber length of the present invention has the best activation effect. The present invention crushes the biomass fibers into dispersed short fibers, which not only facilitates the full contact between the biomass fibers and the activation solution and promotes the formation of pore structures, but also the carrier obtained by the dispersed short fibers after tableting and sintering can better adhere to the coating agent.
[0016] As a preferred solution, the heat activation treatment conditions are: temperature of 60-80°C and time of 1-4h. In the heat activation treatment process of the present invention, the acid-base activation solution is mainly used to destroy the internal structure of the biomass short fiber. The temperature control of the heat activation has an important influence on the activation effect. When the temperature is too low, the activation effect is not obvious or even no activation effect. In the heated state, the activation effect of the acid-base activation solution on the inside of the short fiber is greatly promoted, and functional groups with large surface area and rich functional groups are obtained.
[0017] As a preferred solution, the conditions of the hydrothermal carbonization treatment are: temperature of 150-250°C, time of 18-24h, and pressure of 0.5-2MPa. During the hydrothermal carbonization treatment, on the one hand, high temperature and high pressure can be used to make the acid-base activation solution better penetrate into the internal structure of the biomass short fibers, thereby achieving deep corrosion carbonization of the biomass short fibers; on the other hand, the water molecules in the solution under high temperature and high pressure can promote the formation and expansion of pores in the biomass, thereby promoting the generation of large specific surface and oxygen-containing functional groups. Therefore, the hydrothermal carbonization treatment can further synergistically improve the pore structure and surface functional group content, promote the combination of activated fiber carbon and binder, and make the performance of the carrier more stable. It is further preferred that the temperature of the hydrothermal carbonization treatment is 200-220°C and the carbonization time is 18-20h.
[0018] As a preferred solution, the mass ratio of the activated fiber carbon to the binder is (3-8): (0.1-1); more preferably, the mass ratio of the activated fiber carbon to the binder is (5-6): (0.3-0.5). Experiments have found that under the above preferred mass ratio, the occurrence of hardening can be effectively avoided, further promoting the adhesion of the coating agent, and thus facilitating the regulation of film thickness and hydrophobic antifouling, friction resistance and other properties. When the amount of binder is too low, the activated fiber carbon cannot be formed, and when the amount of binder is too high, hardening will occur.
[0019] As a preferred solution, the binder is at least one of water glass, phenolic resin, asphalt and polyvinyl alcohol.
[0020] As a preferred scheme, the mass ratio of the fiber carbon disc to the coating agent is (10-20): (2-5); at the preferred mass ratio, an effective isolation layer can be formed on the carrier, and it is further preferred that the mass ratio of the fiber carbon disc to the coating agent is (13-15): 3.
[0021] As a preferred solution, the coating agent is ZS-1071 high temperature resistant inorganic adhesive.
[0022] As a preferred solution, the high temperature sintering conditions are: temperature of 600-1000°C, time of 1-4h, and at least one atmosphere of nitrogen, hydrogen and carbon monoxide. Further preferably, the high temperature sintering temperature is 800-900°C, the sintering time is 2-3h, and the sintering atmosphere is a hydrogen-nitrogen mixture. Experiments have found that under the above preferred high temperature sintering conditions, it is beneficial to further enrich the pore structure and molding degree of the fiber carbon disc and improve the ability to adhere to the coating agent; in addition, the oxygen-containing functional groups can be further removed under high temperature conditions, which is beneficial to improve the stability of the coating carrier.
[0023] As a preferred solution, the ratio of the thickness of the top cut off along the thickness direction to the total thickness of the fiber carbon disc is (1-1.5): (6-7). The present invention facilitates the infiltration of the reagent into the disc through the top during the vacuum evaporation coating process by cutting off the top; if the thickness cut off is too much, the amount of reagent attached to the carrier will be reduced.
[0024] The present invention provides a method for preparing a tablet-type carbonaceous coated carrier, which specifically comprises the following preparation steps:
[0025] S1: The biomass fibers are crushed into short fibers, and then dispersed into an activation solution for thermal activation treatment, and then transferred into a hydrothermal reactor for hydrothermal carbonization treatment, and activated fiber carbon is obtained after grinding, washing, and drying;
[0026] S2: Add a binder to the activated fiber carbon, mix them evenly under the action of anhydrous ethanol, and then press them into discs with a diameter of 1.5 to 1.7 cm and a thickness of 6 to 8 mm through a mold, and then transfer them to a tube furnace for high-temperature sintering, and wash and dry them to obtain fiber carbon discs;
[0027] S3: Arrange the above fiber carbon discs neatly, apply coating agent evenly on the surface, perform overall coating and sealing treatment, and cut off the top along the thickness direction after drying to obtain.
[0028] The present invention also provides a tablet-type carbonaceous coated carrier obtained by the above preparation method. The carrier has excellent stability and durability, and after repeated use, the coated carrier can still maintain good physical and chemical properties.
[0029] Finally, the present invention also provides an application of a tablet-type carbonaceous coating carrier, which is used as a coating carrier in vacuum evaporation coating, which not only reduces the loss of medicine and pill breakage during vacuum packaging, but also greatly improves the stability and reusability of the coating carrier while ensuring the coating performance.
[0030] The process parameters of vacuum evaporation coating are: plasma treatment for 3 to 5 minutes, voltage 65 to 68V, current 2.5 to 3A; electron gun preheating power 10% to 15%, silicon plating 10 to 14nm, turntable rotation 99.9%, and the three-stage voltage ratio of evaporation A:B:C is 20.5%:22.1%:22.1%.
[0031] Compared with the prior art, the beneficial effects of the present invention are:
[0032] 1) Through the preparation method provided by the present invention, especially the coordinated treatment of thermal activation and hydrothermal carbonization in the early stage, the fiber carbon is successfully endowed with rich pore structure and oxygen-containing functional groups, which significantly improves the binding with the binder, so that it can achieve the purpose of strong binding under the action of a very small amount of binder, thereby helping to improve the adhesion ability of the coating agent. In addition, by using a coating agent for coating and sealing treatment, not only can an effective isolation layer be formed on the surface of the carrier to prevent the spillage of the coating agent, but also the crucible to which the coating agent is dripped can be effectively avoided. Loss, rupture and other problems during the vacuum packaging process, improve the reusability of the coating carrier.
[0033] 2) The preparation method of the present invention endows the coating carrier with excellent stability and durability. After repeated use, the coating carrier can still maintain good physical and chemical properties and continue to be used as an effective carrier for evaporation operation. This feature not only reduces production costs, but also reduces the generation of waste, which is in line with the development trend of green environmental protection.
[0034] 3) The preparation method of the present invention has clear steps and is easy to operate, and can realize the preparation of the film-coated carrier without complicated equipment and expensive raw materials. This simple and easy-to-use preparation method greatly reduces production costs and improves production efficiency, so that the film-coated carrier has broad application prospects and market competitiveness in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the XRD spectrum of the tablet-type carbonaceous coated carrier prepared in Example 1.
[0036] Figure 2 This is a graph showing the results of a cycle experiment of the tablet-type carbonaceous coated carrier prepared in Example 1.
[0037] Figure 3 1 and 2 are evaporation curves of Example 1, Comparative Example 1 and Comparative Example 6 during evaporation operations. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with the embodiments, which can enable those skilled in the art to more fully understand the present invention, but does not limit the present invention in any way.
[0039] Example 1
[0040] The present invention provides a method for preparing a tablet-type carbonaceous coated carrier, which specifically comprises the following preparation steps:
[0041] S1: The reed straw was crushed into short fibers (about 1 mm in length), and then 3 parts were dispersed in 60 parts of sulfuric acid solution (the mass ratio of sulfuric acid to water was 5:3) for thermal activation at 80°C for 3 hours. Then, the reed straw was transferred to a hydrothermal reactor for hydrothermal carbonization at 220°C for 18 hours and at a pressure of 1 MPa. After completion, the reed straw was ground, washed and dried to obtain activated fiber carbon.
[0042] S2: 0.4 parts of water glass were added to 5 parts of activated fiber carbon, mixed evenly under the action of anhydrous ethanol, and then pressed into a disc with a diameter of 1.5 cm and a thickness of 6 mm through a mold, and then transferred to a tube furnace for high-temperature sintering at a temperature of 800°C and a sintering time of 2 h. The sintering atmosphere was a hydrogen-nitrogen mixed gas (the flow ratio of hydrogen and nitrogen was 2:8), and the fiber carbon disc was obtained after washing and drying;
[0043] S3: Take 15 portions of the above-mentioned fiber carbon discs and arrange them neatly, apply 3 portions of ZS-1071 high temperature resistant inorganic adhesive evenly to the four sides of the discs for coating and sealing, cut off one side of the top of the disc after drying (the thickness cut along the thickness direction is 1 mm) to obtain a tablet-type carbonaceous coated carrier.
[0044] The tablet-type carbonaceous coating carrier obtained in Example 1 was used for the evaporation experiment, and the evaporation process parameters were: plasma treatment for 3 minutes, voltage 65V, current 3A; electron gun preheating power 15%, silicon plating 12nm, turntable rotation 99.9%, evaporation A: B: C three-stage voltage ratio of 20.5%: 22.1%: 22.1%. After the substrate to be coated was left to stand and cleaned and dried, the initial test of the water contact angle was carried out, and the result was recorded as the initial angle. Then, the friction resistance test was carried out using rubber and steel wool respectively. Among them, the number of rubber frictions was 8k times, and the number of steel wool frictions was 5k (steel wool was replaced after 1k frictions). After the test was completed, the water contact angle was recorded again. The test results show that compared with the traditional steel wool carrier, the coating carrier does not affect the coating performance. The initial contact angle of the coated substrate and the contact angle after 8000 rubber frictions and 5000 steel wool frictions are shown in Table 1.
[0045] Example 2
[0046] This embodiment provides a method for preparing a tablet-shaped carbonaceous coated carrier, which specifically includes the following preparation steps:
[0047] S1: The bamboo chips were crushed into short fibers (about 3 mm in length), and then 5 parts were dispersed in 80 parts of sodium hydroxide solution (the mass ratio of sodium hydroxide to water was 3:7) for thermal activation at 60°C for 3 hours. Then, they were transferred to a hydrothermal reactor for hydrothermal carbonization at 200°C for 24 hours and at a pressure of 0.5 MPa. After completion, they were ground, washed and dried to obtain activated fiber carbon.
[0048] S2: 0.7 parts of polyvinyl alcohol (purchased from Aladdin, product number P139540) was added dropwise to 6 parts of activated fiber carbon, mixed evenly under the action of anhydrous ethanol, and then pressed into a disc with a diameter of 1.5 cm and a thickness of 6 mm through a mold, and then transferred to a tube furnace for high-temperature sintering at a temperature of 800°C and a sintering time of 2 h in a hydrogen atmosphere, and then washed and dried to obtain a fiber carbon disc;
[0049] S3: Take 15 portions of the above-mentioned fiber carbon discs and arrange them neatly, apply 4 portions of coating agent evenly to four sides of the discs for coating and sealing treatment, cut off one side of the top of the disc after drying (the thickness cut along the thickness direction is 1 mm) to obtain a tablet-type carbonaceous coated carrier.
[0050] The coating experiment was carried out in the manner of Example 1. The initial contact angle of the coated substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.
[0051] Example 3
[0052] This embodiment provides a method for preparing a tablet-shaped carbonaceous coated carrier, which specifically includes the following preparation steps:
[0053] S1: Coconut shells were crushed into short fibers (about 1 mm in length), and then 5 parts were dispersed in 50 parts of phosphoric acid solution (the mass ratio of phosphoric acid to water was 8:2) for thermal activation at 60°C for 2 hours, and then transferred to a hydrothermal reactor for hydrothermal carbonization at 200°C for 24 hours at a pressure of 2 MPa. After completion, they were ground, washed and dried to obtain activated fiber carbon.
[0054] S2: 0.5 parts of polyvinyl alcohol (purchased from Aladdin, product number P139540) was added dropwise to 5 parts of activated fiber carbon, mixed evenly under the action of anhydrous ethanol, and then pressed into a disc with a diameter of 1.5 cm and a thickness of 6 mm through a mold, and then transferred to a tube furnace for high-temperature sintering at a temperature of 900°C and a sintering time of 3 h in a nitrogen atmosphere, and then washed and dried to obtain a fiber carbon disc;
[0055] S3: Take 15 portions of the above-mentioned fiber carbon discs and arrange them neatly, apply 4 portions of coating agent evenly to four sides of the discs for coating and sealing treatment, cut off one side of the top of the disc after drying (the thickness cut along the thickness direction is 1 mm) to obtain a tablet-type carbonaceous coated carrier.
[0056] The coating experiment was carried out in the manner of Example 1. The initial contact angle of the coated substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.
[0057] Example 4
[0058] This embodiment provides a method for preparing a tablet-shaped carbonaceous coated carrier, which specifically includes the following preparation steps:
[0059] S1: Grind the cotton stalks into short fibers (about 2 mm in length), then take 4 parts and disperse them into 60 parts of nitric acid solution (the mass ratio of nitric acid to water is 2:5) for thermal activation treatment at 60°C for 1 hour, and then transfer them to a hydrothermal reactor for hydrothermal carbonization treatment at 200°C for 20 hours at a pressure of 1 MPa. After completion, grind, wash and dry to obtain activated fiber carbon;
[0060] S2: 0.4 parts of phenolic resin (purchased from Aladdin, product number P195710) were added dropwise to 5 parts of activated fiber carbon, mixed evenly under the action of anhydrous ethanol, and then pressed into a disc with a diameter of 1.5 cm and a thickness of 7 mm through a mold, and then transferred to a tube furnace for high-temperature sintering at a temperature of 800°C and a sintering time of 2 h in a sintering atmosphere of carbon monoxide gas, and then washed and dried to obtain a fiber carbon disc;
[0061] S3: Take 10 portions of the above-mentioned fiber carbon discs and arrange them neatly, apply 3 portions of coating agent evenly to four sides of the discs for coating and sealing treatment, cut off one side of the top of the disc after drying (the thickness cut along the thickness direction is 1.2 mm) to obtain a tablet-type carbonaceous coated carrier.
[0062] The coating experiment was carried out in the manner of Example 1. The initial contact angle of the coated substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.
[0063] Example 5
[0064] Compared with Example 1, the only difference is that the high temperature sintering temperature of 800°C is changed to 1000°C, and the other preparation steps are the same.
[0065] The coating experiment was carried out in the manner of Example 1. The initial contact angle of the coated substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.
[0066] Example 6
[0067] The material of Example 1 was recovered, rinsed with anhydrous ethanol and dried, and the coating experiment was carried out again in the manner of Example 1, and this was repeated 5 times to explore its cyclic stability performance. The initial contact angle of the coated substrate and the contact angle after 8000 times of rubber friction and 5000 times of steel wool friction are shown in Figure 1. Figure 2 shown.
[0068] Comparative Example 1
[0069] Compared with Example 1, the difference is that the reed straw is replaced with waste rubber, and the other preparation steps are the same.
[0070] The coating experiment was carried out in the manner of Example 1. The initial contact angle of the coated substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.
[0071] Comparative Example 2
[0072] Compared with Example 1, the difference is that the activation solution is replaced with deionized water, and the other preparation steps are the same.
[0073] The coating experiment was carried out in the manner of Example 1. The initial contact angle of the coated substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.
[0074] Comparative Example 3
[0075] Compared with Example 1, the difference is that the carbonization treatment is not carried out in a hydrothermal reactor, but is directly heated to 220° C. in a muffle furnace, and the other preparation steps are the same.
[0076] The coating experiment was carried out in the manner of Example 1. The initial contact angle of the coated substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.
[0077] Comparative Example 4
[0078] Compared with Example 1, the difference is that the thermal activation temperature is changed to room temperature, and the other preparation steps are the same.
[0079] The coating experiment was carried out in the manner of Example 1. The initial contact angle of the coated substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.
[0080] Comparative Example 5
[0081] Compared with Example 1, the difference is that no closed coating treatment is performed after high-temperature sintering, and the other preparation steps are the same.
[0082] The coating experiment was carried out in the manner of Example 1. The initial contact angle of the coated substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.
[0083] Comparative Example 6
[0084] The coating experiment was carried out using a traditional steel wool crucible. The initial contact angle of the coated substrate and the contact angle after being rubbed with rubber for 8000 times and with steel wool for 5000 times are shown in Table 1.
[0085] Hydrophobic angle test method: The static contact angle of the coating is measured by a JGW-360a contact angle meter. The test liquid volume is 2μL, the test environment is 24±1℃, and the relative humidity is 45±1%. The water droplet touch angle is measured at 5 points and the average value is taken.
[0086] Rubber abrasion resistance test method: The rubber abrasion resistance test is measured by ZJ-339-GSR wear tester. The coated substrate is fixed on the tester, the pressure is set to 1000g, the stroke is set to 40mm, and the speed is 40cycles / min. After the test, the substrate water drop angle test results are recorded.
[0087] Steel wool abrasion resistance test method: The steel wool abrasion resistance test is measured by ZJ-339-GSR wear tester. The coated substrate is fixed on the tester. The rubber model is MUNBANGSAWOO, the pressure is set to 1000g, the stroke is set to 40mm, the speed is 40cycles / min, and the substrate water drop angle test result 3002 is recorded after the test is completed.
[0088] Table 1 Contact angle of coated substrates under different experimental conditions
[0089]
[0090]
[0091] As shown in Table 1, from the data of Examples 1 to 5 and Comparative Example 6, it can be seen that the carbon disc-shaped coating carrier is not inferior to the traditional steel wool coating carrier in coating performance, and even shows a more excellent effect. Among them, the carbon disc-shaped coating carrier prepared by Example 1 has more excellent comprehensive performance. Figure 2It can be seen that the carbon disc-shaped coating carrier showed good performance in 5 cycle experiments and has excellent reusability. From the data of comparative examples 1 to 5, it can be seen that through the preparation method provided by the present invention, especially the coordinated treatment of thermal activation and hydrothermal carbonization in the early stage, the fiber carbon is successfully endowed with a rich pore structure and oxygen-containing functional groups, which significantly improves the binding with the binder, so that it can achieve the purpose of firm bonding under the action of a very small amount of binder, thereby helping to improve the adhesion ability of the coating agent. In addition, by using a coating agent for coating treatment, not only can an effective isolation layer be formed to prevent the overflow of the coating agent, but also the crucible to which the coating agent is dripped can be effectively avoided. Loss, rupture and other problems during the vacuum packaging process, and the reusability of the coating carrier is improved.
[0092] In addition, the surface crystal composition of the tablet-type carbonaceous film-coated carrier prepared in Example 1 was analyzed by XRD, and the results were as follows: Figure 1 As shown. It can be found that the XRD spectrum shows obvious carbon bulges and does not show the characteristic peaks of crystals with other structures. Figure 3 It can be seen that the evaporation performance of the tablet-type carbonaceous carrier prepared in Example 1 is not significantly different from that of the traditional steel wool carrier, and has better repeatability and contact angle, indicating that the carrier can replace the steel wool carrier for evaporation operation. When waste rubber is used to replace the biomass fiber of the present invention, the evaporation curve has obvious differences.
[0093] The above embodiments are only for better explanation of the principles and practical applications of the present invention, so that those skilled in the relevant technical field can better understand and utilize the present invention, but they are not intended to limit the patent scope of the present invention. All equivalent changes made using the contents of the present invention are within the patent protection scope of the present invention.
Claims
1. A method for preparing a tablet-type carbonaceous coating carrier, characterized in that: The biomass fibers are crushed into short fibers and dispersed into an activation solution for sequential heat activation treatment and hydrothermal carbonization treatment to obtain activated fiber carbon; the activated fiber carbon is mixed with a binder, pressed into shape, and sintered at high temperature to obtain fiber carbon discs; a coating agent is applied to the surface of the fiber carbon disc for overall coating and sealing treatment, and the top is cut off along the thickness direction after drying to obtain the obtained fiber carbon disc.
2. The method for preparing a tablet-type carbonaceous coating carrier according to claim 1, characterized in that: The biomass fiber is at least one of bamboo fiber, reed straw fiber, ramie straw fiber, cotton stalk fiber and coconut shell fiber.
3. The method for preparing a tablet-type carbonaceous coating carrier according to claim 1 or 2, characterized in that: The activation solution contains at least one activator selected from sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, hydrogen peroxide, sodium hydroxide and potassium hydroxide, and the mass ratio of the activator to water in the activation solution is (1-10):(2-10).
4. The method for preparing a tablet-type carbonaceous coating carrier according to claim 3, characterized in that: The mass ratio of the biomass fiber to the activation solution is (1-10): (50-80); The length of the short fibers is 1 to 3 mm.
5. The method for preparing a tablet-type carbonaceous coating carrier according to claim 1, characterized in that: The heat activation treatment conditions are: temperature of 60-80°C and time of 1-4h; The conditions of the hydrothermal carbonization treatment are: temperature of 150-250° C., time of 18-24 h, and pressure of 0.5-2 MPa.
6. The method for preparing a tablet-type carbonaceous coating carrier according to claim 5, characterized in that: The mass ratio of the activated fiber carbon to the binder is (3-8): (0.1-1); The binder is at least one of water glass, phenolic resin, asphalt and polyvinyl alcohol; The mass ratio of the fiber carbon disc to the coating agent is (10-20): (2-5); The coating agent is ZS-1071 high temperature resistant inorganic adhesive.
7. The method for preparing a tablet-type carbonaceous coating carrier according to claim 6, characterized in that: The high temperature sintering conditions are: a temperature of 600-1000° C., a time of 1-4 hours, and an atmosphere of at least one of nitrogen, hydrogen and carbon monoxide.
8. A method for preparing a tablet-type carbonaceous coating carrier according to claim 1, 2, 4, 5, 6 or 7, characterized in that: The ratio of the thickness of the top cut off along the thickness direction to the total thickness of the fiber carbon disc is (1-1.5): (6-7).
9. A tablet-shaped carbonaceous coating carrier, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 8.
10. The use of a tablet-shaped carbonaceous coating carrier according to claim 9, characterized in that: As a coating carrier, it is used in vacuum evaporation coating.
Citation Information
Patent Citations
Enzyme immobilization method by taking carbon fibers as novel carriers
CN101831420A
Pretreatment method of carbon carrier for battery catalyst and carbon carrier
CN112331862A
Graphitized carbon carrier for hydrogen fuel cell, preparation method of graphitized carbon carrier and cell catalyst of graphitized carbon carrier
CN113506885A
Preparation method of vacuum coating pill carrier
CN114310184A